2008
DOI: 10.3748/wjg.14.1919
|View full text |Cite
|
Sign up to set email alerts
|

Changes of ghrelin following oral glucose tolerance test in obese children with insulin resistance

Abstract: In conclusion, in obese children with insulin resistance, ghrelin levels decreased with advancing pubertal stage. Ghrelin secretion suppression following OGTT was influenced by gender and pubertal stage. Baseline ghrelin levels and ghrelin suppression after OGTT did not significantly correlate with the degree of insulin resistance and insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In a study it was reported that ghrelin levels decreased with the advancing pubertal stage in obese children with insulin resistance. This study also showed that suppression of ghrelin secretion following oral glucose tolerance test was influenced by the pubertal stage (23). Another study demonstrated the ghrelin levels inversely correlated with luteinizing hormone and testosterone levels (24).…”
Section: Ghrelinsupporting
confidence: 54%
“…In a study it was reported that ghrelin levels decreased with the advancing pubertal stage in obese children with insulin resistance. This study also showed that suppression of ghrelin secretion following oral glucose tolerance test was influenced by the pubertal stage (23). Another study demonstrated the ghrelin levels inversely correlated with luteinizing hormone and testosterone levels (24).…”
Section: Ghrelinsupporting
confidence: 54%
“…Human studies suggest that insulin exerts an inhibitory effect on ghrelin secretion since plasma ghrelin and insulin levels show an inverse relationship at the time of food intake and during an euglycemia clamp [29]. Another human study showed a lack of significant correlation of systemic ghrelin with insulin changes in response to an OGTT in obese children with insulin resistance [30]. Additionally, in rats with streptozotocin-induced diabetes, plasma ghrelin levels decreased following a meal in spite of a blunted rise in systemic insulin levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, plasma levels of ghrelin in obese children were compared with those of normal weight controls. Generally, the plasma ghrelin concentration of obese children is lower in fasting condition [ 6 10 ], whereas the decline in response to glucose ingestion varies as a function of insulin sensitivity; the decline appears to be less profound in insulin resistant obese children [ 6 , 11 ], although the data are equivocal [ 12 ]. Weight loss tends to normalize circulating ghrelin levels [ 8 , 10 , 13 ], although this is still a subject for debate [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%